REPRESENTASI BUDAYA LOKAL DALAM KEGIATAN DENPASAR FESTIVAL DI KOTA DENPASAR - Eka Juliawati, Ni Putu (E-Jurnal Kajian Budaya (Online Journal of Cultural Studies); Volume 01, Nomor 01, Desember 2012)
This paper discusses the representation of local culture in Denpasar Festival. Denpasar Festival is Denpasar’s Government annual agenda which aimed at reviving the local culture of Denpasar which more and more faded because it undermined by globalization. The increasing arrival of tourists and migrants have been destabilizing the existence of Denpasar local culture. Denpasar Festival was serving traditional cuisine, dance and performing arts and traditional textiles. Based on this background, the problem of this study is what were the implications of the representation of local culture in Denpasar Festival? This study was a qualitative interpretative research. The data were collected through field observations, interviews and literature study. The theories used were the representation theory and theory of deconstruction. As a result of this study, it was found that Denpasar Festival has implications for the social, cultural and economic fields.
Keywords: representation, local culture, festival